Bioactive films based on cuttlefish (Sepia officinalis) skin gelatin incorporated with cuttlefish protein hydrolysates: Physicochemical characterization and antioxidant properties. (June 2020) - Kchaou, Hela; Jridi, Mourad; Benbettaieb, Nasreddine; Debeaufort, Frédéric; Nasri, Moncef
Graphical abstract: Highlights: Cuttlefish skin valorized by gelatin, protein isolate and hydrolysates extraction. Protein isolate and hydrolysates enriched gelatin films were successfully prepared. Physical-chemical and antioxidant properties of films were evaluated. Lower mechanical properties and higher hydrophilicity for hydrolysates added films. Enriched films are colored and displayed higher UV barrier and antioxidant potential. Abstract: The objective of this study was to apply cuttlefish ( Sepia officinalis ) skin protein isolate (CSPI) and hydrolysates (CSPH), using commercial Savinase® and Purafect® enzymes, as bioactive additives in the elaboration of gelatin-based films. CSPH and CSPI enriched films were colored and exhibited a higher UV-barrier properties compared to gelatin film. In addition, compared to CSPI added film, an increase of the glass transition temperature by 20 % and 4 %, respectively, for Purafect and Savinase hydrolysates enriched films was noted. However, elongation at break decreased significantly for CSPH incorporated films by 2.5-fold. The tensile strength was reduced by 28.2 % and 44.4 % for Purafect and Savinase hydrolysates added films, respectively. Furthermore, a decrease of water contact angle by 45 % and 51 % for films added with Purafect and Savinase hydrolysates, respectively, was displayed compared to gelatin film. Interestingly, CSPH enriched films also displayed higher antioxidant potential than control gelatin films evaluated by several in vitro assays.